Robotic waste sorting using deep learning - Goorun Yurisha; Marais Stephen; Nicolls Fred (MATEC Web of Conferences)
The ongoing waste crisis has highlighted the need to address the problem of waste collection and sorting. This paper presents an automated waste sorting system with Deep Learning using a stereoscopic camera and a robotic manipulator. The system can recognise and classify different types of waste and sort them into specific categories by using the robotic arm to improve the recycling process.